2010
DOI: 10.1021/ja1048048
|View full text |Cite
|
Sign up to set email alerts
|

Direct Analysis of Donor−Acceptor Distance and Relationship to Isotope Effects and the Force Constant for Barrier Compression in Enzymatic H-Tunneling Reactions

Abstract: The role of dynamical effects in enzyme catalysis is both complex and widely debated. Understanding how dynamics can influence the barrier to an enzyme catalyzed reaction requires the development of new methodologies and tools. In particular compressive dynamicsthe focus of this studymay decrease both the height and width of a reaction barrier. By making targeted mutations in the active site of morphinone reductase we are able to alter the equilibrium of conformational states for the reactive complex in turn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
156
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 75 publications
(162 citation statements)
references
References 55 publications
(153 reference statements)
6
156
0
Order By: Relevance
“…Heavy isotope labeling is expected to reduce the frequencies of harmonic bond vibrations, while having minimal effect on electrostatics. In enzymes where vibrations lead to active site 'compression' such as the transient reduction in hydrogen donor-acceptor atoms, which has been suggested for OYEs such as PETNR, 1,25,[39][40][41] then perturbation of such vibrations can lead to altered reaction kinetics by altering the probability of transition state formation and/or the rate of transition state recrossing. 17,18,42 Slower dynamics will also be affected by mass perturbation, which may lead to altered substrate/product binding and release kinetics.…”
Section: Resultsmentioning
confidence: 99%
“…Heavy isotope labeling is expected to reduce the frequencies of harmonic bond vibrations, while having minimal effect on electrostatics. In enzymes where vibrations lead to active site 'compression' such as the transient reduction in hydrogen donor-acceptor atoms, which has been suggested for OYEs such as PETNR, 1,25,[39][40][41] then perturbation of such vibrations can lead to altered reaction kinetics by altering the probability of transition state formation and/or the rate of transition state recrossing. 17,18,42 Slower dynamics will also be affected by mass perturbation, which may lead to altered substrate/product binding and release kinetics.…”
Section: Resultsmentioning
confidence: 99%
“…This can be accomplished in two distinct ways. The reduced distance can be reached via a local, picosecond-nanosecond timescale distance sampling contribution to the reorganization barrier (29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40). Evidence for distance sampling has been obtained repeatedly from highly temperature-dependent kinetic isotope effects and has been discussed extensively in the literature (refs.…”
Section: Discussionmentioning
confidence: 99%
“…The finding that the KIEs, including the isotope effects on the Arrhenius pre-factor (that indicate the tunneling in the reaction, see below) observed in the presence of added cations differ significantly from the KIEs observed in the absence of cations presented a direct evidence of an influence of cations on the PCET process. Within the framework of the Marcus-like tunneling model [40 -60], the observed changes in KIE can be viewed as a consequence of changes in both barrier height and width due to the changes both in the donorÀacceptor distance for Htransfer and the force constant of compressive modes coincident with the reaction coordinate [55] [56] [59] [60], resulting from interactions of ionic environment with the activated complex in the reaction (see also below). The observations are: in the Na þ concentration range, the prevailing reaction channel probably is that involving the cation in a proximity of the activated complex in the PCET reaction, although the cation in the solvent cage is neither the redox partner nor involved in the proton transfer in the reaction.…”
mentioning
confidence: 99%
“…It has also been shown [57] that a modification of the model can be applied to a system that does not involve a protein environment. Scrutton and co-workers [59] [60] have suggested that compressive modes (the donorÀacceptor distance fluctuations coincident and coupled with the reaction coordinate, promoting modes) may be a feature of both solution and enzyme systems.…”
mentioning
confidence: 99%